Income inequality between overlapping and stratification: a longitudinal analysis of personal earnings in France and Italy. Issue 5 (2nd September 2016) - Castellano, Rosalia; Manna, Rosalba; Punzo, Gennaro
Abstract: The aim of this paper is to gain new insights into the generation process of personal income in France and Italy, two countries that are in close geographical proximity but have a large disparity in terms of income growth and distribution. In the first step, the potential of EU-SILC balanced panel (2004–2007) is exploited by random effects models, which also make it possible to explore the primary factors that are likely to explain differences in generating personal labour earnings. In the second step, the ANOGI (Analysis of Gini) decomposition enables one to assess the contribution of each sub-population to overall income inequality and the degree to which each subgroup is stratified. A joint evaluation of income determinants gives evidence of the high complexity of inequality process and throws light on the role of gender, skill levels and job characteristics in determining different degrees of income stratification. Indeed, although the high heterogeneity among members of a same subgroup (within-group inequality) explains a large share of overall income inequality, the between-group inequality becomes significant in explaining the income differentials between employment status and occupation types.